[(3a+1)x]/3=[a(x-4)]/4(x是未知数)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 01:32:43
[(3a+1)x]/3=[a(x-4)]/4(x是未知数)[(3a+1)x]/3=[a(x-4)]/4(x是未知数)[(3a+1)x]/3=[a(x-4)]/4(x是未知数)[(3a+1)x]/3=[
[(3a+1)x]/3=[a(x-4)]/4(x是未知数)
[(3a+1)x]/3=[a(x-4)]/4(x是未知数)
[(3a+1)x]/3=[a(x-4)]/4(x是未知数)
[(3a+1)x]/3=[a(x-4)]/4
4(3a+1)x=3ax-12a
12ax-3ax+4x=-12a
9ax+4x=-12a
(9a+4)x=-12a
x=-12a/(9a+4)
-a/(a+1/12)
f(x)=(3a-1)x+4a,x
f(x)=(3a-1)x+4a,x
f(x)=(3a-1)x+4a,x
a+x/x+1 ,x/x^2-2x-3 ,a/x^2+4x+3
集合A={y/y=1-x-4/x},B={X/X^2-(3+a)X+3a
集合A={y|y=1-x-(4/x)},B={x|x^2-(3+a)x+3a
计算:1/(a-x)-1/(a+x)-2x/(a^2+x^2)-4x^3/(a^4+x^4)
f(x)=(4a-3)x+1-2a,x属于[0,1],f(X)
a^2x=根号2-1,则(a^3x+a^-3x)/(a^x+a^-x)=?
若a^2x=√2 -1,则(a^3x+a^-3x)/(a^x+a^-x)等于?
已知a^2x=根号2+1,求(a^3x+a^-3x)/(a^x+a^-x)
a^2x=根号2-1 ,则a^x+a^-x/a^3x+a^-3x等于..
已知a^(2x)=根号2-1,求a^(3x)+a^(-3x)/a^x+a^(-x)
已知a^2x=根号2+1求(a^3X+a^-3X)/(a^X+a^-X)
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
不等式(a-3a-4)x-(a-4)x-1
x^2 -(4a-1)x+3a^2 -a